Mechanism of Coal Bump among Mine Group under the Control of Large Geological Body: A Case Study of Yima Mining Area, China - Yizhe Li; Shankun Zhao; Qingxin Qi; Pengzhi Pan; Xiangzhi Wei; Yin Wang; Ningbo Zhang; Yang Zhao; Haitao Chai; Qilin Hao (Advances in Civil Engineering)
Coal bump often occurs in coal mining among many working faces in mine group under the control of large geological bodies. In order to study the coal bump mechanism between adjacent working faces under the conditions of large fault and huge thick overburden conglomerate, this paper regards Yima mining area as a practical engineering background and theoretically analyzes the mechanical behavior of overlying rock in the spatial structure. Then, the deep-ground and whole-space measurement is carried out in the 13230 working face of Gengcun mine and 21121 working face of Qianqiu mine. The results show that the basic structural unit in Yima mining area is composed of two goafs, middle coal pillar, and overlying conglomerate. Under the condition of nonsynchronous mining in adjacent working faces, there is a comovement effect similar to lever’s “prying” phenomenon in thick conglomerate beam—the conglomerate strata above larger goaf side induce an overall uplift movement of the corresponding strata above smaller goaf side, and uplift length of the conglomerate strata is related to the mining length, coal pillar width, caving angle, and coal-conglomerate distance. The results of surface subsidence, microseism, and stress in the two working faces verify the conglomerate’s phenomenon of comovement effect and disturbance range and further explain the role of active movement of F16 fault and overall causes of huge thick conglomerate on the coal bump. The vertical stress of the 13230 face is relatively low at the beginning, and high horizontal stress by fault activation causes typical bump accident with the horizontal sliding of coal body. With the increasing development of 13230 face, the intensity and frequency of coal bump in horizontal direction decrease obviously, but with high proportion in vertical direction. The results provide a theoretical basis for the study on the mechanism of coal bump between two adjacent working faces under the conditions of huge thick conglomerate and large thrust fault.